Assessment of Indoor Air Quality and Influential Factors: A Study in Rural Areas of Solan District, Himachal Pradesh (India) - Thakur, Komal; Brahmi, Mohinder Kumar; Dogra, Karina; Bhanwala, Vivek; Tomar, Sakshi (International Journal of Bio-resource and Stress Management, 2024)
The study was conducted during December, 2020 to June, 2021 to assess indoor air quality (IAQ) and develop amelioration strategies in rural areas of the Solan district, located in Himachal Pradesh, India. A well-structured pre-tested questionnaire was used to assess the factors responsible for indoor air quality.The indoor air quality parameters including PM10, Non-Respirable Suspended Particulate Matter (NRSPM), Total Suspended Particulate Matter (TSPM), Nitrogen dioxide (NO2) and Sulfur dioxide (SO2)were studied to calculate air quality index.The findings revealed substantial variation in pollution levels among different villages. Nauni village had the highest concentration of pollutants, with PM10 levels at 24.17 µg m3-1, NRSPM at 20.37 µg m3-1, TSPM at 44.54 µg m3-1, NO2 at 12.54 µg m3-1 and SO2 at 0.35 µg m3-1. In contrast, Nagali village has the lowest levels of these contaminants. Despite variations, all recorded values were within permissible limits. Nine factors were identified as contributing to poor indoor air quality: fuel wood-based cooking, smoke sources, mode of ventilation, insect/pest control measures, waste disposal near the house, use of perfumes and air freshners, cowshed near the house, intermittent cleaning, and dampness in the house due to leakage. To reduce indoor air pollution in rural areas, the study suggests establishing concentrated methods that address these specific issues. Proper ventilation, alternate cooking methods and better waste management procedures are important steps in improving indoor air quality and protecting public health.